One, Two, Three: A Bioorthogonal Triple Labelling Strategy for Studying the Dynamics of Plant Cell Wall Formation In Vivo. Issue 51 (21st November 2018) - Simon, Clemence; Lion, Cedric; Spriet, Corentin; Baldacci‐Cresp, Fabien; Hawkins, Simon; Biot, Christophe
Abstract: Reported herein is an in vivo triple labelling strategy to monitor the formation of plant cell walls. Based on a combination of copper‐catalysed alkyne–azide cycloaddition (CuAAC), strain‐promoted azide–alkyne cycloaddition (SPAAC), and Diels–Alder reaction with inverse electronic demand (DARinv ), this methodology can be applied to various plant species of interest in research. It allowed detection of the differential incorporation of alkynyl‐, azido‐, and methylcyclopropenyl‐tagged reporters of the three main monolignols into de novo biosynthesized lignin in different tissues, cell types, or cell wall layers. In addition, this triple labelling was implemented with different classes of chemical reporters, using two monolignol reporters in conjunction with alkynylfucose to simultaneously monitor the biosynthesis of lignin and non‐cellulosic polysaccharides. This allowed observation of their deposition occurring contemporaneously in the same cell wall. Abstract : One, two, three : A triple bioorthogonal labelling strategy was developed to study the incorporation of three distinct monolignol reporters in lignin within plant cell walls. Alkynylfucose was also used in conjunction with monolignol reporters to show that non‐cellulosic polysaccharide and lignin deposition can occur contemporaneously in the same cell wall. CuAAC: copper‐catalysed alkyne–azide cycloaddition, SPAAC: strain‐promoted azide–alkyne cycloaddition, DARinv : Diels–Alder reaction with inverse electronic demand.